Influence of information, gender and emotional status for detecting small differences in the acceptance of a new healthy beverage - Rocha Parra, Diego F. (2015)
Fil: Rocha Parra, Diego F. Pontificia Universidad Católica Argentina. Facultad de Ciencias Agrarias; Argentina